Memahami dan Mengukur Kecerdasan Logis Matematis: Sebuah Telaah Pustaka - Zakiatun Hana; Nujumuddin Nujumuddin; Ramdhani Sucilestari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
One of the internal factors that can affect student learning outcomes is intelligence. Intelligence is the most important psychological factor in the learning process and determines the quality of student learning. So far mathematical logical intelligence is still the main benchmark for the level of intelligence of each individual and is a strong indicator in the learning achievement of students. Therefore, the profile, relationships and effects of mathematical logical intelligence need to be revealed. There have been many studies related to the relationship and influence of mathematical logical intelligence that have been carried out and published in journals and proceedings. A literature review of the results of these studies has been carried out. The conclusion that can be drawn from this literature is that the mathematical logical intelligence profile of students in Indonesia is at a moderate to good level. The relationship and influence of logical-mathematical intelligence that has been revealed is more on variables related to cognitive and affective domains, so it needs to be disclosed for variables in the psychomotor domain. Finally, the selection of intelligence measurement instruments must pay attention to the type of intelligence to be measured and the criteria for intelligence development based on age.